Functional Tumor Volume by Fast Dynamic Contrast‐Enhanced MRI for Predicting Neoadjuvant Systemic Therapy Response in Triple‐Negative Breast Cancer - Musall, Benjamin C.; Abdelhafez, Abeer H.; Adrada, Beatriz E.; Candelaria, Rosalind P.; Mohamed, Rania M.M.; Boge, Medine; Le‐Petross, Huong; Arribas, Elsa; Lane, Deanna L.; Spak, David A.; Leung, Jessica W.T.; Hwang, Ken‐Pin; et al. (Journal of magnetic resonance imaging, 2021)
Background Dynamic contrast‐enhanced (DCE) MRI is useful for diagnosis and assessment of treatment response in breast cancer. Fast DCE MRI offers a higher sampling rate of contrast enhancement curves in comparison to conventional DCE MRI, potentially characterizing tumor perfusion kinetics more accurately for measurement of functional tumor volume (FTV) as a predictor of treatment response. Purpose To investigate FTV by fast DCE MRI as a predictor of neoadjuvant systemic therapy (NAST) response in triple‐negative breast cancer (TNBC). Study Type Prospective. Population/Subjects Sixty patients with biopsy‐confirmed TNBC between December 2016 and September 2020. Field Strength/Sequence A 3.0 T/3D fast spoiled gradient echo‐based DCE MRI Assessment Patients underwent MRI at baseline and after four cycles (C4) of NAST, followed by definitive surgery. DCE subtraction images were analyzed in consensus by two breast radiologists with 5 (A.H.A.) and 2 (H.S.M.) years of experience. Tumor volumes (TV) were measured on early and late subtractions. Tumors were segmented on 1 and 2.5‐minute early phases subtractions and FTV was determined using optimized signal enhancement thresholds. Interpolated enhancement curves from segmented voxels were used to determine optimal early phase timing. Statistical Tests Tumor volumes were compared between patients who had a pathologic complete response (pCR) and those who did not using the area under the receiver operating curve (AUC) and Mann–Whitney U test. Results About 26 of 60 patients (43%) had pCR. FTV at 1 minute after injection at C4 provided the best discrimination between pCR and non‐pCR, with AUC (95% confidence interval [CI]) = 0.85 (0.74,0.95) (P < 0.05). The 1‐minute timing was optimal for FTV measurements at C4 and for the change between C4 and baseline. TV from the early phase at C4 also yielded a good AUC (95%CI) of 0.82 (0.71,0.93) (P < 0.05). Data Conclusion FTV and TV measured at 1 minute after injection can predict response to NAST in TNBC. Level of Evidence 1 Technical Efficacy 4